2019
DOI: 10.1186/s12933-019-0885-2
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between frailty and mortality, hospitalization, and cardiovascular diseases in diabetes: a systematic review and meta-analysis

Abstract: Background In patients with diabetes, death and cardiovascular diseases are attributed to classical risk factors such as hypertension, dyslipidemia, and smoking habit, whereas these events are attributed to frailty in the remaining patients. In this meta-analysis, we examined the relationship between frailty and mortality, hospitalization, and cardiovascular diseases in patients with diabetes. Methods Literature search was conducted using databases such as MEDLINE, Coch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(76 citation statements)
references
References 46 publications
3
65
1
2
Order By: Relevance
“…Patients with diabetes and the features of Frailty are more likely to develop urolithiasis [ 20 ]. According to the results of the meta-analysis conducted by Ida et al in patients living with diabetes there is a relationship between the incidence of Frailty and the mortality and risk of hospitalization [ 22 ].…”
Section: Frailtymentioning
confidence: 99%
“…Patients with diabetes and the features of Frailty are more likely to develop urolithiasis [ 20 ]. According to the results of the meta-analysis conducted by Ida et al in patients living with diabetes there is a relationship between the incidence of Frailty and the mortality and risk of hospitalization [ 22 ].…”
Section: Frailtymentioning
confidence: 99%
“…This loss is accelerated in elderly individuals [2, 3]. Sarcopenia is associated with a decrease in the activities of daily living, a decrease in quality of life, and cardiovascular diseases [46]. Previous studies have shown that the frequency of sarcopenia is higher in patients with diabetes than that in patients without diabetes [7].…”
Section: Introductionmentioning
confidence: 99%
“…A study in 2016 reported that avoidable hospitalisation increased by a factor of 1.35 for each additional chronic condition and 1.55 for each additional body system affected 40 , 41 . Clearly, a chronic disease cohort is particularly susceptible to recurrent hospitalisations and, while digitisation may play role in changing healthcare delivery, hospital departmental factors (e.g., seniority of clinician reviewing, busyness of department, community service delivery) and external factors (e.g., patient education and activation, behavioural insights towards digitisation, social support available) are likely to significantly contribute and may impact widespread deployment of novel digital technologies 42 .…”
Section: Discussionmentioning
confidence: 99%